Detecting changes in arabidopsis cell wall composition using time‐of‐flight secondary ion mass spectrometry. (12th March 2015) - Tsai, Alex Yi‐Lin; Goacher, Robyn E.; Master, Emma R.
Abstract : Time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) was previously used to characterize lignocellulosic materials, including woody biomass. ToF‐SIMS can acquire both rapid spectral and spatial information about a sample's surface composition. In the present study, ToF‐SIMS was used to characterize the cell walls of stem tissue from the plant model organism, Arabidopsis thaliana . Using principal component analyses, ToF‐SIMS spectra from A . thaliana wild‐type (Col‐0), cellulose mutant ( irx3 ), and lignin mutant ( fah1 ) stem tissues were distinguished using ToF‐SIMS peaks annotated for wood‐derived lignocellulose, where spectra from the irx3 and fah1 were characterized by comparatively low polysaccharide and syringyl lignin content, respectively. Spatial analyses using ToF‐SIMS imaging furthermore differentiated interfascicular fiber and xylem vessels based on differences in the lignin content of corresponding cell walls. These new data support the applicability of ToF‐SIMS peak annotations based on woody biomass for herbaceous plants, including model plant systems like arabidopsis. Copyright © 2015 John Wiley & Sons, Ltd.